The direct electrocatalytic oxidation of ammonia by copper-deposited nickel foam catalysts. (1st April 2023) - Tsai, Ming-Han; Juang, Yaju; Hu, Chi-Chang; Hua, Lap-Cuong; Mahata, Biplab Kumar; Huang, Chihpin
Highlights: Cu plated on Ni foam (NF) showed higher activity to NH3 oxidation than bare NF. Decreases in initial pH and applied potential favored electrooxidation of NH3 to N2 . N product selectivity was affected by the Ni/Cu ratio and electrolysis parameters. A high Cu(I) proportion formed on the Cu/NF electrode favored the N2 formation. Abstract: The electrochemical oxidation process is a green and efficient strategy for ammonia removal from wastewater. Here, we investigated the direct ammonia electrochemical oxidation (AEO) and selectivity of nitrogen products (e.g. SN2, SNO2 −, SNO3 − ) using Cu-deposited nickel foam (Cu/NF) electrode at initial pHs of 8−11 and applied electrode potentials of 0.7−1.1 V vs. Hg/HgO for a 5-h AEO reaction. The electrochemical analysis showed that Cu/NF exhibited a higher current density of 3 mA cm −2 and a larger specific capacitance of 380 µF cm −2 than those obtained by pristine NF (1.4 mA cm −2 and 210 µF cm −2 ) under the presence of NH3 . Cu/NF performed a high NH3 removal and conversion of NH3 to NO3 −, accounted for >50% and >90%, at initial pHs > 9.5 and applied electrode potentials > 0.9 V. X-ray photoelectron spectroscopy (XPS) analysis confirmed that Cu(II) and Ni(III) were electrochemically formed in the form of CuNi oxyhydroxide during the AEO reaction. At an initial pH 11 and an electrode potential of 0.9 V, the decrease of the Cu(I) proportion in the Cu(I)/Cu(II) speciation of CuNi oxyhydroxide (from 42% at 1st h to 7.2%) decreased the SN2 from 71% to 33% after the 5-h electrolysis. Furthermore, an increase of Ni/Cu ratio in the NiCu oxyhydroxyl species also favored the production of N2 . The findings of this study reveal that a precise control of initial pH and electrode potential is able to alter the NiCu oxyhydroxyl species on the Cu/NF electrode surface during the AEO reaction, changing the NH3 conversion pathways. Graphical abstract: Image, graphical abstract